Laparoscopic subtotal cholecystectomy in patients with acute cholecystitis - Al-aubaidi, Tariq I.; Abid-AlKadhim, Anwar A.; Sbahi, Khalid R. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Using Laparoscopic approach, Cholecystectomy is made hazardous by distortion of the anatomy of Calot's triangle by acute or chronic inflammation and dense omental adhesions. Laparoscopic subtotal cholecystectomy (LSTC) without cystic duct ligation is an alternative to conversion to open surgery in difficult cases.Results: Fifty cases of LSTC were performed, 32 of them were males and the remaining 18 patients were females. The age of study group was ranged (18 – 75) years with a median of (46) year. The median operating time was about 90 min. and the mean duration of hospital stay was 7.3±2.2 days. There were 8 patients (16%) with postoperative bile leak, most of them recover spontaneously and only 2 patients (4%) underwent postoperative ERCP and stent insertion for persistent bile leak. 4 patients (8%) with postoperative wound infection and 2 (4%) with postoperativechest infection due to bile leak and longer operating time.1 patient (2%) with subphrenic collection which mandates open drainage for cure. No mortality was recorded in our study.Methods: This prospective study included 50 patients with different forms of clinical presentations subjected to LSTC at the 2nd floor in Baghdad Teaching Hospital and conducted during a period from Jan. 1st, 2010 to Dec. 31st, 2012.Conclusion: LSTC is an alternative to open conversion in cases with Calot's triangle difficult anatomy and dissection is hazardous. And is associated with avoidance of any injury to biliary passages in spite of longer operating time.